ABO and Rhesus Types of Blood Group Distribution in Blood Donors in Blood Bank, Government Medical College and Hospital-Suryapet, Telangana: A Tertiary Care Centre Study - Dr. Madhukar Reddy Kadaru; Dr. K. Raja Kumar; Dr. D. Smitha Reddy (Tropical Journal of Pathology and Microbiology, 2019)
Aims and objectives: To study the distribution and frequencies of ABO and Rhesus (Rh) blood groups among blood donors, who participated in indoor and outdoor blood donation camps organized by suryapet blood bank, Government medical college-suryapet, Telangana. ABO and Rh typing is very important for proper functioning and safe blood banking. Materials and Methods: A Three-year retrospective study was carried out at suryapet blood bank, Telangana, during 3-year period from January 2016 to December 2018 and the total number of blood units collected was 7,035. The donors were screened and who are medically fit are accepted for blood donation. Blood group of the blood donors was determined by forward grouping and reverse grouping methods with the help of commercially available standard monoclonal antisera. Results: The most common blood group among donors was “O” (43.90%) followed by “ B” (32.50%), “A” (17.95%) and the least prevalent blood group was “AB” (05.62%). Maximum number of blood donors were Rh positive (95.72%) while Rh negative were only (04.27%). There was a higher rate of male donors than female donors. Conclusion: The present study concludes that most common blood group was “O” positive and the least common is “AB”. This data helps in appropriate maintenance of inventory in the blood bank and also plays important role in patients health care.